Goblet cell differentiation in human colorectal cancer cell lines - Liu, H (2017)
Goblet cells are one of the three fully differentiated lineages in human colonic crypts. They play an important role in protecting epithelial cells from direct contact with luminal contents by secreting mucus, which consists of MUC2, TFF3 and other constituents. The goblet cell differentiation, however, is largely dysregulated in human colorectal cancers. Abundant expression of MUC2 is often observed in signet ring carcinomas and mucinous carcinomas that are associated with unsatisfactory prognosis. Despite the significant roles of goblet cells, its genetic nature and exact regulatory mechanisms remain incompletely understood. In this thesis, the goblet cell differentiation at mRNA and protein levels was characterised in a panel of 64 human colorectal cancer cell lines. Microarray analysis on the bulk population of these cell lines reveals the genes differentially expressed in goblet cell-positive cell lines, including AKR1B10, AGR3 and the cellular surface protein CA12 (Chapter 3). In addition, a novel protocol is developed for isolation and sequencing of RNA from the fixed and FACS purified cells. Using this protocol, the first goblet cell transcriptome is profiled in LS180 cancer cell line, and the goblet cell-specific genes are identified, including TFF3 and SPDEF (Chapter 4). The co-expression patterns of TFF3 and MUC2 is further investigated. In a subset of cancer cell lines, TFF3 recognises the goblet cells that cannot produce MUC2, suggesting additional regulatory mechanisms are required for its expression. The dysregulated regulation of TFF3 may provide additional evidence in colorectal cancer classification. The transcriptional regulation of ATOH1 and SPDEF on goblet cell differentiation is also demonstrated. Knock-down of either transcriptional factor decreases the goblet cell numbers, while double knock-down completely depletes goblet cell formation, suggesting the co-operative regulation of SPDEF and ATOH1 on goblet cell differentiation. In addition, CA12-positive but not -negative cells can give rise to goblet cells with the expression of MUC2, TFF3 and SPDEF. This indicates CA12 may act as a potential cellular surface marker to identify goblet cell progenitors (Chapter 5). In summary, this thesis screens goblet cells in colorectal cancer cell lines and characterise the first goblet cell transcriptome, which provides the foundation to understand regulatory control of goblet cell differentiation.